An Inclusive Psychoanalyst: Sidney Blatt's Contribution In Perspective. (June 2017) - Berman, Emanuel
Sidney Blatt personified in many ways the striving toward an inclusive, broad-minded, nonsectarian, and nondogmatic psychoanalysis. Intrigued and inspired by many trends in psychoanalytic thought and neighboring disciplines, he believed deeply in the coexistence and mutual contributions of a psychoanalytic clinical practice and of systematic empirical research on development and its disruptions, evolving personality traits, and the ways psychoanalytic treatment becomes effective. Carl Rogers, David Rapaport, and John Bowlby were among the figures who played a significant role in the development of his rich and complex thinking and productive work.